FAKTOR âFAKTOR YANG MEMPENGARUHI KEANDALAN DAN KETEPATAN WAKTU PELAPORAN KEUANGAN (Study Empiris Pada SKPD Pemda Riau) (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2014)
This study aims to test the influence human resources, information technology,internal control and local financial monitoring to reliability and timeliness localgovernment financial reporting. Research sample is an heads and staffs of SKPDâsaccounting department in Riau Province, Dumai City, Bengkalis district and Kampardistrict. Data collection was done by providing 361 questionnaires to heads andstaffs of SKPDâs accounting department. The collected data was processed usingSPSS version 17 with multiple linier regressions. Results of research show thesignificant effects of human resources, internal control and local financial monitoringon reliability of local government financial reporting, while information technologyhas no effect. The study results also show that human resources and informationtechnology affect significant on timeliness of local government financial reporting.Keywords: Human Resources, Information Technology, Accounting Internal Control,Local Financial Monitoring, Reliability and Timeliness Local GovernmentFinancial Reporting